2010
DOI: 10.1111/j.1551-2916.2010.03859.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Behavior of SiO2–Al2O3–ZnO–CaO Glass System at 1123–1273 K

Abstract: The crystallization characteristics of a glass, used as the matrix of high‐temperature protective coatings, based on SiO2–Al2O3–ZnO–CaO with the addition of TiO2 and ZrO2 at a temperature range of 1123–1273 K have been investigated. At 1273 and 1173 K, tetragonal zirconia doped with Ti and Ca, initially precipitated from the melt. At 1123 K, however, zirconolite instead of zirconia precipitated as the primary phase. The secondary precipitates were zircon and titanite in the glass fired at 1273 K, titanite and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 40 publications
(64 reference statements)
2
22
0
Order By: Relevance
“…Additionally, diffraction peaks of tetragonal and monoclinic zirconia are found in the XRD patterns after sintering at 1000 1C for 1 h. However, they disappeared after sintering for 20 h. Instead, peaks of zircon appeared. This confirmed that the formation of zircon was due to the reaction between the base glass and the zirconia precipitates, which was consistent with our previous studies [33,41]. Diffraction peaks of zirconolite and albite were not found in the XRD patterns after sintering at 1000 1C for either 1 h or 20 h. Phase evolution of E30A specimens at 900 1C and 1000 1C is shown in Fig.…”
Section: Phase Evolution Of Al 2 O 3 /Glass Compositessupporting
confidence: 94%
See 3 more Smart Citations
“…Additionally, diffraction peaks of tetragonal and monoclinic zirconia are found in the XRD patterns after sintering at 1000 1C for 1 h. However, they disappeared after sintering for 20 h. Instead, peaks of zircon appeared. This confirmed that the formation of zircon was due to the reaction between the base glass and the zirconia precipitates, which was consistent with our previous studies [33,41]. Diffraction peaks of zirconolite and albite were not found in the XRD patterns after sintering at 1000 1C for either 1 h or 20 h. Phase evolution of E30A specimens at 900 1C and 1000 1C is shown in Fig.…”
Section: Phase Evolution Of Al 2 O 3 /Glass Compositessupporting
confidence: 94%
“…At temperatures of 900-1000 1C, elements of Ca and Ti were likely to segregate together and form titanite (nominally CaTiSiO 5 ) in the base glass [33,41]. However, CaZrTi 2 O 7 instead of CaTiSiO 5 was detected for E10A and E30A specimens sintered at 900 1C.…”
Section: Effect Of Al 2 O 3 On Phase Evolution Of Base Glassmentioning
confidence: 82%
See 2 more Smart Citations
“…This phenomenon implies an interdependent relationship between a-quartz and b-cristobalite, which provides a further evidence to indicate the transformation of a-quartz particles to b-cristobalite phase in the coating. Besides, the detected low intensity zircon was the precipitates of the glass matrix [29,40].…”
Section: Evolution Of the Interfacial Structurementioning
confidence: 97%